Keunggulan Agronomi Empat Calon Varietas Hibrida F1 Mentimun (Cucumis sativus L.) Tipe Lalap - Galih Wahyu Septiawan; Annisa Khoiriyah; Asih Farmia (Universitas Tidar, 2026)
The development of superior cucumber (Cucumis sativus L.) varieties requires the identification of distinctive morphological characteristics and superior agronomic performance to support cultivar selection and release. This study aimed to identify the morphological characteristics and evaluate the agronomic superiority of four candidate F1 hybrid cucumber varieties for fresh consumption compared with one commercial check variety. The experiment was conducted from February to May 2026 at PT. Tani Murni Jogja using a non-factorial Randomized Complete Block Design with five treatments and four replications. Morphological traits were evaluated descriptively according to the Distinctness, Uniformity, and Stability (DUS) testing guidelines, whereas agronomic traits were analyzed using analysis of variance (ANOVA) followed by the 5% Honestly Significant Difference (HSD) test. The results revealed morphological variation in leaf orientation, young fruit spine density, fruit base shape, and fruit tip shape, while the remaining traits were relatively uniform among the tested genotypes. Variety significantly affected most agronomic traits, including stem length, stem diameter, leaf length, leaf width, flowering age, fruit length, fruit diameter, flesh thickness, number of fruits per plant, and fruit weight. Among the tested genotypes, TL-03 and TL-04 exhibited the most balanced agronomic performance and are considered the most promising candidates for further evaluation and development as superior fresh-market cucumber varieties.Keywords: Cucumber, morphological characterization, agronomic traits, F1 hybrid, superior variety